Future research directions and global research trends of applying artificial intelligence in human resources using bibliometric analysis - Alkoud, Saleh; Majeed, Isam; Zainudin, Dolhadi; Mhd. Sarif, Suhaimi (Human Resource Management Academic Research Society (HRMARS), 2024)
The study aims to highlight the future research directions and global research trends of applying artificial intelligence (AI) in Human Resources (AI) Using Bibliometric Analysis in the last three decades (1996–2024). Using performance analysis and scientific mapping, the research uses bibliometric analysis to investigate co-authorship, co-occurrence, citation, bibliographic coupling and co-citation analysis in 99 articles taken from the Scopus database. The analysis looked at the quantity of scientific publications, the most prolific writers, the most important papers, nations, and organizations. The study used VOSviewer as a science mapping and performance analysis tool. The most productive year was 2023 with 34 publications and the most impactful institute and countries are the Essec Business School in France, and the country is the United States, respectively. Similarly, the most influential journal is “California Management Review”, furthermore, the most cited article is “Artificial intelligence in human resources management: Challenges and A path forward”. The authors also identified four thematic clusters of Research on Artificial Intelligence in Human Resources, the four theme groupings are Artificial Intelligence, Human Resource Management, Human Capital Complementarity, and AI Capability Framework. It presents academic direction and information about the current state and future study in the field of artificial intelligence literature in human resources. This study enhances the theoretical comprehension of AI's impact on HR by providing a thorough examination of worldwide patterns and real-world implementations. It promotes the use of AI frameworks in line with strategic HR objectives